Small RNA and Transcriptome Sequencing Reveal a Potential miRNA-Mediated Interaction Network That Functions during Somatic Embryogenesis in Lilium pumilum DC. Fisch. - Zhang, Jing; Xue, Bingyang; Gai, Meizhu; Song, Shengli; Jia, Nana; Sun, Hongmei (Frontiers in Plant Science, 2017)
Plant somatic embryos are widely used in the fields of germplasm conservation, breeding for genetic engineering and artificial seed production. MicroRNAs (miRNAs) play pivotal roles in somatic embryogenesis (SE) regulation. However, their regulatory roles during various stages of SE remain unclear. In this study, six types of embryogenic samples of Lilium pumilum DC. Fisch., including organogenic callus, embryogenic callus induced for 4 weeks, embryogenic callus induced for 6 weeks, globular embryos, torpedo embryos and cotyledon embryos, were prepared for small RNA sequencing. The results revealed a total of 2,378,760 small RNA reads, among which the most common size was 24 nt. Four hundred and fifty-two known miRNAs, belonging to more than 86 families, 57 novel miRNAs and 40 miRNA*s were identified. The 86 known miRNA families were sorted according to an alignment with their homologs across 24 land plants into the following four categories: 23 highly conserved, 4 moderately conserved, 15 less conserved and 44 species-specific miRNAs. Differentially expressed known miRNAs were identified during various stages of SE. Subsequently, the expression levels of 12 differentially expressed miRNAs and 4 targets were validated using qRT-PCR. In addition, six samples were mixed in equal amounts for transcript sequencing, and the sequencing data were used as transcripts for miRNA target prediction. A total of 66,422 unigenes with an average length of 800 bp were assembled from 56,258,974 raw reads. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment indicated that 38,004 and 15,497 unigenes were successfully assigned to GO terms and KEGG pathways, respectively. Among the unigenes, 2,182 transcripts were predicted to be targets for 396 known miRNAs. The potential targets of the identified miRNAs were mostly classified into the following GO terms: cell, binding and metabolic process. Enriched KEGG analysis demonstrated that carbohydrate metabolism was the predominant pathway in Lilium SE. Thus, we performed systemic characterization, homology comparisons and profiling of miRNA expression, and we constructed an miRNA-target network during Lilium SE for the first time. Our findings establish a foundation for the further exploration of critical genes and elucidation of SE in Lilium.